Waktu Berjemur Terbaik Untuk Meningkatkan Vitamin D dalam Pencegahan Coronavirus Disease (Covid-19) - Joewono, Muliani (JURNAL MEDIA KESEHATAN, 2021)
Background: The Coronavirus mostly attacks people with low immune systems and can results in death. Adequate vitamin D can increase immunity. Most of the Indonesian population is deficient in vitamin D. Exposure to sunlight can increase vitamin D however inappropriate and long hours causes many health problems. Aim Of This Paper: is to determine the best sunbathing time to increase vitamin D in the prevention of Coronavirus Disease 2019 (covid-19). Discussion: Optimal sun exposure in various areas, influenced by environmental and human factors. Most of the Indonesian population needs 1 minimal erythemal dose (MED) which can be obtained by sunbathing at 11:00 a.m. to 14:00 p.m. for 37.5 – 64.5 minutes a day but is more risky causing health problems than before 10:00 a.m. According to Perdoski, sunbathe started from 9 to 10 a.m. for 15 minutes a day or until the skin turns pink, 2-3 times a week with at least 22.5 % area of the body exposed is sufficient and safer. Conclusion: sunbathing from 9:00-10:00 a.m., maximum 15 minutes or skin starts pink, 2-3 times a week is sufficient to increase vitamin D and prevent Covid-19. Wearing a hat and sunscreen is still recommended.